Effect of Pilocarpine Hydrochloride on the Schlemm Canal in Healthy Eyes and Eyes With Open-Angle Glaucoma - Skaat, Alon; Rosman, Michael S; Chien, Jason L; Mogil, Rachel S; Ren, Ruojin; Liebmann, Jeffrey M; Ritch, Robert; Park, Sung Chul (JAMA ophthalmology, 2016)
The in vivo effect of pilocarpine hydrochloride on the Schlemm canal may help explain its pharmacologic mechanism of action and better indicate its clinical use. To investigate the effect of pilocarpine on the structure of the Schlemm canal in vivo in healthy eyes and eyes with glaucoma. In this case-control study, healthy individuals and patients with open-angle glaucoma were prospectively enrolled between September 1, 2013, and June 30, 2014, after a complete ophthalmologic examination at a tertiary glaucoma referral practice. Eighty-one serial, horizontal, enhanced depth imaging optical coherence tomographic B-scans (interval between B-scans, approximately 35 µm) of the nasal corneoscleral limbus were performed before and 1 hour after topical administration of pilocarpine, 1%, in 1 eye of healthy volunteers and pilocarpine, 2%, in 1 eye of patients with glaucoma. Fifty B-scans in the overlapping area (circumferential length, approximately 1.7 mm) between the 2 sets of serial scans (before and after pilocarpine administration) were selected for analysis based on the structures of aqueous and blood vessels as landmarks. The cross-sectional area of the Schlemm canal was measured in each selected B-scan. Volume of the Schlemm canal was calculated using commercially available 3-dimensional reconstruction software. Mean cross-sectional area of the Schlemm canal. Enhanced depth imaging optical coherence tomographic scans of the Schlemm canal were performed successfully before and after administration of pilocarpine, 1%, in 9 healthy eyes (9 individuals) and pilocarpine, 2%, in 10 eyes with glaucoma (10 patients) (mean [SD] age, 31.9 [7.8] and 68.7 [13.2] years, respectively). Following pilocarpine administration, mean (SD) intraocular pressure decreased from 14.3 (1.3) to 13.7 (1.1) mm Hg in healthy eyes (P = .004) and from 17.5 (6.0) to 16.6 (6.1) mm Hg in eyes with glaucoma (P = .01). The mean (SD) cross-sectional area of the Schlemm canal increased by 21% (4667 [1704] to 5647 [1911] µm2) in healthy eyes (P < .001) and by 24% (3737 [679] to 4619 [692] µm2) in eyes with glaucoma (P < .001) (mean difference in percent increase, 2.2%; 95% CI, -8.5% to 12.9%). The mean (SD) volume of the Schlemm canal in the overlapping area increased from 8 004 000 (2 923 000) to 9 685 000 (3 277 000) µm3 in healthy eyes (P < .001) and from 6 468 000 (1 170 000) to 7 970 000 (1 199 000) µm3 in eyes with glaucoma (P < .001). These data suggest that pilocarpine expands the Schlemm canal in eyes with and without glaucoma. No differences in the effect were identified between the 2 groups. Enhanced depth imaging optical coherence tomography may be useful in investigating the effect of pharmacologic agents on the Schlemm canal.